1987
DOI: 10.1080/02652038709373649
|View full text |Cite
|
Sign up to set email alerts
|

HPLC determination of the total content of aflatoxins in naturally contaminated eggs in free and conjugate forms

Abstract: A study was undertaken to evaluate the total aflatoxin content in naturally contaminated eggs. Two pools of eggs from laying hens were collected after 2 and 7 days of treatment with aflatoxin B1 (AFB1). An HPLC method has been developed for the determination of AFB1, aflatoxin M1 (AFM1), aflatoxin B2a (AFB2a) and aflatoxicol (Ro) both in free form and after release from water-soluble conjugates. The bound form was cleaned up after acid hydrolysis of the aqueous phase. Eggs collected after 2 days of treatment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
0
11
1
2
Order By: Relevance
“…Similarly, Wolzak et al (1985) and Micco et al (1987) only observed detectable levels of AFM 1 in hens' eggs after 4 and 7 days, respectively, thus suggesting that the formation of AFM 1 is not a significant pathway during the first days of aflatoxin treatment of laying birds. However, in the present study, the concentrations of AFM 1 were in the range 0.03-0.37 mg kg À1 and the highest levels were found in eggs from treatment with 100 mg AFB 1 kg À1 , particularly after 60 days of continuous ingestion of the contaminated diet.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Similarly, Wolzak et al (1985) and Micco et al (1987) only observed detectable levels of AFM 1 in hens' eggs after 4 and 7 days, respectively, thus suggesting that the formation of AFM 1 is not a significant pathway during the first days of aflatoxin treatment of laying birds. However, in the present study, the concentrations of AFM 1 were in the range 0.03-0.37 mg kg À1 and the highest levels were found in eggs from treatment with 100 mg AFB 1 kg À1 , particularly after 60 days of continuous ingestion of the contaminated diet.…”
Section: Resultsmentioning
confidence: 61%
“…Extraction and quantification procedures followed 649 Aflatoxin residues in eggs of laying Japanese quail the method recommended by the Association of Official Analytical Chemists-978.15 (Scott 1990), including modifications as described by Wolzak et al (1985) and Micco et al (1987). Each lot of 32 eggs was pooled (egg white plus yolk) in a blender jar and blended 1 min at moderate speed.…”
Section: Analysis Of Aflatoxin B 1 Residues In Eggsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residues of OTA are detected in tissues such as liver, kidneys, muscles, eggs, and plasma of OTA-fed poultry birds (Frye and Chu, 1978;Micco et al, 1987;Niemiec et al, 1994;…”
Section: Introductionmentioning
confidence: 99%
“…The order of aflatoxin toxicity (AFB 1 >AFG 1 >AFB 2 >AFG 2 ) seems to be due to the structure of the toxin, especially the terminal furan moiety [3][4][5]. These aflatoxins are present in several commodities such as peanuts, cereals and cottonseeds, whereas aflatoxin M 1, which is just as toxic as aflatoxin B 1 [6], is most often analyzed in milk and dairy products.…”
mentioning
confidence: 99%